Detection of Clostridium botulinum neurotoxin genes (A–F) in dairy farms from Northern Germany using PCR: A case-control study. (June 2016) - Fohler, Svenja; Discher, Sabrina; Jordan, Eva; Seyboldt, Christian; Klein, Guenter; Neubauer, Heinrich; Hoedemaker, Martina; Scheu, Theresa; Campe, Amely; Charlotte Jensen, Katharina; Abdulmawjood, Amir
Abstract: Classical botulism in cattle mainly occurs after ingestion of feed contaminated with preformed toxin. In 2001 a form of botulism ("visceral botulism") was postulated to occur after ingestion of Clostridium ( C. ) botulinum cells or spores, followed by colonization of the intestine, and local production of botulinum neurotoxin (BoNT) causing chronic generalized disease. To verify the potential role of C. botulinum in the described syndrome, a case-control study was conducted, including 139 farms. Fecal samples, rumen content, water and silage samples were collected on each farm. Real time BoNT gene PCR assays were conducted after enrichment in RCM (Reinforced Clostridial Medium) at 37 °C and conventional PCRs after enrichment in MCM (Modified Cooked Meat Medium) at 30 °C. Furthermore, a direct detection of BoNT genes without prior enrichment was attempted. BoNT A, B, C, D, E and F genes were detected in animal samples from 25 (17.99%), 3 (2.16%), 0 (0.0%), 2 (1.44%), 1 (0.72%), and 3 (2.16%) farms, respectively. Eleven feed samples were positive for BoNT A gene. By enrichment a significant increase in sensitivity was achieved. Therefore, this should be an essential part of any protocol. No significant differences regarding BoNT gene occurrence could be observed between Case and Control farms or chronically diseased and clinically healthy animals within the particular category. Thus, the postulated form of chronic botulism in cows could not be confirmed. This study supports the general opinion that C. botulinum can occasionally be found in the rumen and intestine of cows without causing disease. Highlights: Case-control study to verify the role of C. botulinum in chronic disease in dairy cattle. C. botulinum neurotoxin genes of types A, B, D, E and F were detected. No differences regarding neurotoxin gene detection between case and control farms.